Patterns of postpartum home visit and their relationship with maternal well-being and self-efficacy, exclusive breastfeeding duration, infant weight gain and completion of immunization - Ngaya-an, Floreliz V. (Manila College of Nursing, University of the Philippines Manila, 2015)
The study investigated on the home visiting activity of the health workers in Bustos, Bulacan, looking into pattern, actions, and outcomes on: maternal well-being and self-efficacy, exclusive breastfeeding duration, infant weight gain, and completion of immunization. This study employed the Mixed Methods Research, wherein the researcher collected, integrated, and analyzed both quantitative data. The findings from both methods of inquiry are triangulated to develop a cogent and logical interpretation of the results.
Prospective cohort design was utilized for the quantitative inquiry. Women in their third trimester of pregnancy were recruited as participants of the study. Purposive sampling was done, inclusion criteria were: 1) residency in Bustos, and 2) being of legal age. There were a total of 137 mother participants in the quantitative inquiry. Beginning from the time of the baby’s birth, these mother and baby dyads were followed through for a period of six months, wherein there were two follow-up visits in order to gather quantitative data, with the use of questionnaires.
Critical Incident Technique (CIT) was used for the qualitative inquiry. The researcher conducted audio-recorded, face to face interviews with mothers who experienced home visit postpartum, and the health workers who do the home visits such as the nurses and the Barangay Health Workers (BHWs). There were a total of four nurses, five BHWs, and ten mother participants. All mother participants were asked ahead of time to write a diary about the home visits. Only diary of mothers who were interviewed face to face were included in the analysis of the qualitative data.
Both quantitative and qualitative findings clearly affirmed the value of home visiting. Mothers identified the need for knowing that they are doing the right thing for themselves and their babies; BHWs and mothers validated how supportive relationships between them built trust and promoted adherence by mothers with their clinic follow-up. Early visit usually by BHWs were associated with the number of immunizations completed by infants. When breastfeeding was discussed with mothers they exclusively breastfed their infants longer. Discussion of immunization with mothers was positively associated with infants’ weight gain suggesting that it is integral to any discussion of infant care. Nursing visits tend to be longer and associated with mothers’ self-efficacy in infant care, and infants’ weight gain. Home visiting can actualize evidence-based care in resource-poor regions when there is sufficient training for BHWs, better ratio of nurses and midwives in the locality, and providing them with portable resources such as supplies and equipment.
Dissertation (Doctor of Philosophy in Nursing) -- University of the Philippines Manila, June 2015.
Bibliography: leaves 115-127.
Keywords: Postnatal care; Infants -- Care